2022
DOI: 10.3233/sji-210855
|View full text |Cite
|
Sign up to set email alerts
|

New recommendation to predict export value using big data and machine learning technique

Abstract: Official statistics on monthly export values have a publicity lag between the current period and the published publication. None of the previous researchers estimated the value of exports for the monthly period. This circumstance is due to limitations in obtaining supporting data that can predict the criteria for the current export value of goods. AIS data is one type of big data that can provide solutions in producing the latest indicators to forecast export values. Statistical Methods and Conventional Machin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Google trend data is still rarely used to predict macroeconomic variables such as inflation, industrial production and others. However, in line with the development of research using google trends data, several literatures/ references were found that conducted research using google trends to predict macroeconomic indicators (Nooraeni et al, 2019). Nuti et al (2014) on the use of google trends in health care research concluded that google trends can be used to study health phenomena in various topic domains.…”
Section: The Use Of Google Trend Analysismentioning
confidence: 95%
“…Google trend data is still rarely used to predict macroeconomic variables such as inflation, industrial production and others. However, in line with the development of research using google trends data, several literatures/ references were found that conducted research using google trends to predict macroeconomic indicators (Nooraeni et al, 2019). Nuti et al (2014) on the use of google trends in health care research concluded that google trends can be used to study health phenomena in various topic domains.…”
Section: The Use Of Google Trend Analysismentioning
confidence: 95%